Hodgkin's lymphoma‐associated vanishing bile duct syndrome successfully treated with radiation as a bridge to chemotherapy. Issue Volume 5:Issues 2(2021) (1st April 2021) - Ebadi, Maryam; Olson, Jeffrey; Bateman, Justin; Mathew, Damien; Yuan, Jianling; Rashidi, Armin
Abstract: Vanishing bile duct syndrome is a paraneoplastic manifestation of Hodgkin's lymphoma that often proves fatal. Treatment of the underlying lymphoma with chemotherapy is a priority, and liver dysfunction is frequently prohibitive. A 27‐year‐old woman presented with severe cholestatic hepatitis that was diagnosed as vanishing bile duct syndrome on liver biopsy. Chest imaging showed mediastinal and supraclavicular lymphadenopathy that was diagnosed as Hodgkin's lymphoma. She was administered involved‐site radiation (3960 cGy), yielding partial lymphoma remission and marked improvement in liver function. Subsequently, standard chemotherapy achieved complete remission. A total of 19 months thereafter, the patient was in complete remission with normal liver function. We conclude that tumor‐directed radiotherapy can be used as a bridge to curative chemotherapy in Hodgkin's lymphoma‐associated vanishing bile duct syndrome. Vanishing bile duct syndrome (VBDS) is a rare and fatal paraneoplastic presentation of Hodgkin lymphoma (HL) In a patient with HL above the diaphragm and paraneoplastic VBDS, involved‐site radiation to the tumor resulted in cytoreduction and improved liver function Curative‐intent chemotherapy was subsequently initiated and led to a complete remission of HL and resolution of liver injury In HL‐associated paraneoplastic VBDS, RT to the tumor can be used as a bridge to curative chemotherapy